Optimasi Jumlah Etil Selulosa dan Kecepatan Pengadukan dalam Preparasi Hollow Microspheres Kaptopril - Eka Deddy Irawan; Taffana Windy Hananta; Dwi Nurahmanto (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Captopril is an Angiotensin-Converting Enzyme inhibitor (ACE Inhibitor) used for the treatment of hypertension. It has been reported that the duration of antihypertensive action after a single oral dose of captopril is only 6–8 h, specific absorption in the stomach, stable at acidic pH and degraded at high pH. These indicate a promising potential of the captopril hollow microspheres system as an alternative to the conventional dosage form. The preparation method used in this study is non-aqueous solvent evaporation. This study aims to determine the amount of ethyl cellulose (EC) and stirring speed to produce hollow microspheres having entrapment efficiency (EE), buoyancy and particle size maximum. Determination of the optimum hollow formula microspheres captopril uses a design factorial of two factors at two levels. The factors used in this study were the amount of EC and stirring speed, while the observed response was EE, buoyancy and particle size. The chosen optimum formula will be verified and characterized (yield, SEM, FT-IR). Formula AB was the optimum formula with EE 90.68%, buoyancy 81.52% and particle size 267.10µm. The verification obtained results in accordance with the prediction of the Design-Expert software. The characterization results obtained a yield value of 98.33%, with a spherical shape, uneven surface morphology, and hollow core. The results of FT-IR analysis showed that there was no interaction between the drug and polymer used in the formulation.